The Relationship Between the Leadership Style of the Head of The Room and The Work Motivation of Nurses in The Internal Medicine Inpatient Room at The Guido Valadares National Hospital, Dili 2022 - Maximiano Oqui; Alexandra Maria Pires; Teresa Vaz Cabral; Sandra Lorena Mira; Miguel Soares; Aureo Frutalegio da Costa Freitas (Rifa'Institute, 2022)
Introduction: Leadership is the ability to exert constructive influence on others to make one cooperative effort to achieve a planned goal. Motivation is something in the form of strength, energy or power, or a complex state and willingness is an impulse in the individual to move towards a certain goal. The motivation of a nurse can also undergo changes caused by factors that affect her. Methods: This research uses correlational quantitative methods, which will be carried out at, Hospital Nacional Guido Valadares Díli. Data collection techniques use questionnaires, data analysis using the Spearman Rank correlational formula. Objective: The purpose of this study is to find out a good leadership style so that the nurse's work motivation increases. Results and Discussion: Of the 48 respondents with orthocratic leadership style with percentage (22%), democratic leadership style with presentation (27%), laissez-faire leadership style with percentage (25%), participatory leadership style with percentage (26%), and from respondents 48 people with good work motivation with a total of 29 people (60.4%), Unkind motivation totaling 2 people (4.2%), moderate motivation 10 (20.8%), Motivation was excellent for 7 people (14.6%). Conclusion: The spearman rank correlation statistical test value gets a result of p=0.037<0.05, the correlation of the coefficient with the value of 0.401 means that there is a significant relationship